Analysis on smallholder preferences on selling their yield at Pertubuhan Peladang Kawasan (PPK), Sri Medan, Batu Pahat, Johor / Muhammad Shah Iskandar Nordin - Nordin, Muhammad Shah Iskandar (Faculty of Plantation and Agrotechnology, 2019)
The fresh fruit bunch (FFB) middlemen sub-sector was part of Malaysia palm oil supply chain. It was interrelated with other sub sectors either directly or indirectly. It served as a intermediary between the smallholder and the millers. Middleman needed to be efficient so that the FFB sent to the mills within 24 hours after harvesting remained in good quality. As the private middlemen , they always took advantage toward the oil palm farmers. Some farmers prefered to sell to private middlemen due to several factors such as transportation, storage and the middlemen offer them higher price than the market price. While smallholder still prefer to selling their oil palm fruit to PPK as them offer affordable price and they provide efficient storage, trustworthy and also incentive. The purpose of the study was to identify the most preferable factor of independent smallholders when they selling their Fresh Fruit Bunch (FFB) at PPK .The study was conducted in several communities at Sri Medan, Batu Pahat. Primary data with structured questionnaire were collected from 200 respondents of smallholder using stratified sampling. Factor Analysis is used to analyse relationship between price of the oil palm, incentive offered by middlemen and government assistance towards smallholder preferences when selling their yield. Based on factor analysis result shown, the value of KMO for this study was 0.867 which is acceptable and reliable for conducting factor analysis . These 3 factor collectively explained 53.937% of the total variation of the factor influencing smallholder preferences when they were selling their Fresh Fruit Bunch (FFB). For this data , Bartlett’s test is highly significant (p<0.001) and therefore factor analysis is appropriate . The study can be useful guide to PPK to improve the smallholder development and income.